Expected Values of Molecular Descriptors in Random Polyphenyl Chains - Zahid Raza; Kiran Naz; Sarfraz Ahmad (Emerging Science Journal, 2022)
A chemical graph is a model used to indicate a chemical combination. In a molecular graph, vertices define atoms, and edges are represented as chemical bonds. A topological index is a single number to characterize the graph of a molecule. In this article, we study the topological properties of some special chains. The polyphenyl chains with hexagons are graphs of aromatic organic compounds. The key purpose of this article is to explore the expected value of Sombor, reduced Sombor, and average Sombor index for this category of organic compounds. It was investigated that the Sombor, reduced Sombor and average Sombor index revealed adequate discriminative potential of alkanes. It has been tested that these indicators can be used effectively in modeling chemical thermodynamic structures. The average value of the Sombor, reduced Sombor, and average Sombor index for the set of all spiro and random polyphenyl chains has been determined. Finally, the ratio between the expected values of these mentioned indices for both random chains has been resolved. Doi: 10.28991/ESJ-2022-06-01-012 Full Text: PDF